Soccer Coaching - Pandu Wiratama; Yendrizal - (Universitas Negeri Padang, 2019)
The problem in this research is soccer coaching. The purpose of this study is to look at the motivation of athletes, coaches, and infrastructure in coaching football. This research is a descriptive quantitative study. The population in this study are all people who are members of MENARA FC. The sampling technique in this study used a total sampling technique, the sample in this study was 28 people. This research was conducted in 3 days, Monday, Tuesday and Thursday. The instruments of this study were observation, interviews, questionnaires, and documentation. Data analysis techniques in this study using the Likers scale. Results of the study: 1) Motivation is needed in coaching athletes. Between the two forms of motivation is more dominant internal motivation even though it is not separated from external motivation in the field or at home. 2) The trainer is very influential in coaching so the trainer must have a good foundation. The trainer already has a license and has participated in FILANESIA training, but cannot carry out the training program that he has made well because of incomplete infrastructure. 3) Infrastructure facilities at MENARA FC are sufficient but still unable to cope with all forms of training provided by the coach, there are still many that must be completed